2021
DOI: 10.1021/jacs.1c01073
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Reductive Cross Coupling and Enantioselective Protonation of Olefins to Construct Remote Stereocenters for Azaarenes

Abstract: A novel enantioselective protonation protocol that is triggered by reductive cross coupling of olefins is reported. When under cooperative photoredox and chiral hydrogen-bonding catalytic conditions and using a terminal reductant, various α-branched vinylketones with diverse vinylazaarenes could provide important enantioenriched azaarene derivatives containing tertiary stereocenters at their remote δ-position with high yields and enantioselectivities. This reaction system is also suitable for α-branched vinyla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
44
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 84 publications
(45 citation statements)
references
References 57 publications
0
44
0
1
Order By: Relevance
“…reported chiral phosphoric acid/photocatalytic asymmetric reductive cross‐coupling between α‐branched vinylketones and vinylazaarenes (Scheme 80). [152] The novelty of the reaction is that highly enantioenriched δ‐stereocenters were formed during the enantioselective protonation step with satisfactory regioselectivity and chemoselectivity. A diverse array of enantioenriched azaarenes were obtained in 35 %–95 % yields and 62 %–99 % ee.…”
Section: Photoredox/chiral Brønsted Acid/base Dual Catalysismentioning
confidence: 99%
See 2 more Smart Citations
“…reported chiral phosphoric acid/photocatalytic asymmetric reductive cross‐coupling between α‐branched vinylketones and vinylazaarenes (Scheme 80). [152] The novelty of the reaction is that highly enantioenriched δ‐stereocenters were formed during the enantioselective protonation step with satisfactory regioselectivity and chemoselectivity. A diverse array of enantioenriched azaarenes were obtained in 35 %–95 % yields and 62 %–99 % ee.…”
Section: Photoredox/chiral Brønsted Acid/base Dual Catalysismentioning
confidence: 99%
“… Catalytic reductive cross‐coupling of α‐branched vinylketones with vinylazaarenes to construct δ‐stereocenters and 1,4‐sterocentres [152] …”
Section: Photoredox/chiral Brønsted Acid/base Dual Catalysismentioning
confidence: 99%
See 1 more Smart Citation
“…The reductive PCET of C=C bonds in α,β-unsaturated carbonyl compounds can also be followed by the formation of a new C-C bond via a radical addition to another alkenes. In 2021, Jiang's group [131] reported a novel strategy in order to access the enantioselective protonation that is triggered by the reductive cross coupling of olefin substrates (Scheme 57). Through this method, under the reaction conditions consist of cooperative photoredox and chiral hydrogen-bonding catalyst, in addition of a terminal reductant, a diverse range of enantioenriched azaarene products with tertiary stereocenters at their δ-position, which are important structures commonly exist in many natural products, could be generated from the corresponding α-branched vinylketones in both high yield and ee.…”
Section: Oxidative Decarboxylationmentioning
confidence: 99%
“…Subsequently, many elegant studies revealed that bifunctional H‐bonding catalysis, that is, with acid and base moieties of chiral catalysts interacting with radicals and reaction partners simultaneously, is more versatile (Scheme 1C) [3, 7] . Among them, our group successfully developed a range of important enantioselective radical addition and radical coupling reactions, [7d–i] in which the construction of enantioenriched imine‐containing azaarene variants was closely watched given the ubiquity of azaarenes in natural products, pharmaceuticals and functional materials. Accordingly, we were interested in tackling the challenging Melchiorre reaction, and N ‐phenylglycine was used as the precursor of the α‐amino radical because it features a H‐bond donor (see below).…”
Section: Introductionmentioning
confidence: 99%